Double Taxation Conventions in Central and Eastern European Countries - DUMITER, Florin; JIMON, Ștefania (Journal of Legal Studies, 2016)
In this article we provide a qualitative overview regarding the panacea of double taxation conventions in Central and Eastern European Countries. Double taxation paradigm highlights some serious problems arising from multiple taxation of the same income or capital. In the European Union these problems suggest that there is a strong need of a "best practice" construction of an optimal fiscal space in order to eliminate or reduce this problem. Central and Eastern European Countries have some special features: on one hand these countries have been influenced by the communist and postcommunism era, and on the other hand there are specific particularities for each country which must be economically and judicially understood and explained. This article highlights the structure, construction and appliance of the double taxation conventions in the Central and Eastern European Countries. The conclusions of this article enact the solutions of the potential problems of double taxation, especially in these former communist countries, with respect to the strengthening of the new fiscal space in the European Union.